High‐molecular‐weight glutenin subunit compositions in current Chinese commercial wheat cultivars and the implication on Chinese wheat breeding for quality. Issue 4 (4th May 2020) - Gao, Song; Sun, Genlou; Liu, Weihua; Sun, Daokun; Peng, Yanchun; Ren, Xifeng
Abstract: Background and objectives: Genetic diversity of high‐molecular‐weight (HMW) glutenin subunits is often used for wheat improvement because of its correlation with end‐use quality of wheat. The objectives were (a) to characterize and analyze the HMW‐GS composition of common wheat, (b) determine the diversity of high‐molecular‐weight glutenin subunits, and (c) elucidate the distribution characteristics of wheat good‐quality subunit and quality classification. Findings: The results revealed a total of 15 different alleles (3 at Glu‐A1, 8 at Glu‐B1, and 4 at Glu‐D1 ) and 35 allele combinations. Glu‐A1c (57.92%), Glu‐A1a (62.94%), Glu‐A1c (55.86%) appeared to be the most frequent alleles at Glu‐A1 in Hebei, Henan, and Sichuan provinces, respectively. The Glu‐B1c was the most common allele at the Glu‐B1 locus in all three provinces, with frequencies of 48.75%, 55.24%, and 29.66%, respectively. Glu‐D1a (66.25%), Glu‐D1d (53.85%), Glu‐D1a (55.17%) at the Glu‐D1 locus appeared to be the common alleles in Hebei, Henan, and Sichuan provinces, respectively. Cluster analysis based on allelic similarity of Glu‐1 loci classified the 528 wheat cultivars into two major categories. Conclusions: These results indicated that the HMW glutenin allele compositions are not optimal for the current varieties in these provinces. A high level of quality improvement may be implemented by increasing the frequencies of Glu‐A1a (1) or Glu‐A1b (2*), Glu‐B1i (17 + 18), Glu‐D1d (5 + 10). Significance and novelty: Our results revealed clear directions for wheat quality improvement in these provinces.